Efficacy of Combined Topical Timolol and Oral Propranolol for Treating Infantile Hemangioma: A Meta-Analysis of Randomized Controlled Trials - Qiao, Junbo; Lin, Junjie; Zhang, Dexin; Li, Junhua; Chen, Changkuan; Yu, Hongye; Li, Xiaodi; Fang, Bin (Frontiers in Pharmacology, 2020)
Background: Oral propranolol has become the first-line treatment for infantile hemangioma (IH). However, combined therapy with topical timolol and oral propranolol has been proposed as a more effective IH treatment strategy. We aimed to compare the safety and efficacy of topical timolol, oral propranolol, and their combination for treating IH in a meta-analysis. Methods: Relevant randomized controlled trials (RCTs) were obtained after searching the PubMed, Embase, Cochrane’s Library, China National Knowledge Infrastructure, and WanFang databases. A random-effect model was used to pool the results. Results: Eight RCTs with 759 patients with IH were included in this meta-analysis. Treatment with topical timolol alone showed a similar response rate compared to oral propranolol (risk ratio [RR] = 0.97, p = 0.63), but resulted in fewer adverse events (RR = 0.36, p = 0.002). Combined treatment with topical timolol and oral propranolol showed a favorable response rate compared to treatment with oral propranolol (RR = 1.14, p = 0.03) or topical timolol (RR = 1.36, p = 0.01) alone. Moreover, combined treatment showed similar risks of adverse events compared to oral propranolol (RR = 0.80, p = 0.24) or topical timolol (RR = 1.31, p = 0.25) alone. Conclusions: Combined treatment with topical timolol and oral propranolol may be more effective than either single treatment strategy in patients with IH. Topical timolol alone conferred similar efficacy for IH compared to oral propranolol, but with less incidence of adverse events.